Neighborhood Environmental Attributes and Adults' Maintenance of Regular Walking. Issue 6 (June 2015) - SUGIYAMA, TAKEMI; SHIBATA, AI; KOOHSARI, MOHAMMAD J.; TANAMAS, STEPHANIE K.; OKA, KOICHIRO; SALMON, JO; DUNSTAN, DAVID W.; OWEN, NEVILLE
ABSTRACT Purpose Environmental initiatives to support walking are keys to noncommunicable disease prevention, but the relevant evidence comes mainly from cross-sectional studies. We examined neighborhood environmental attributes associated cross-sectionally with walking and those associated prospectively with walking maintenance. Methods Data were from the Australian Diabetes, Obesity and Lifestyle study collected in 2004–2005 (baseline) and in 2011–2012 (follow-up). Participants who did not move residence during the study period (n = 2684, age range: 30–77 yr at baseline) were categorized as regular walkers (walked five times per week or more) or not at baseline. Regular walkers were divided into those who stopped and those who maintained regular walking at follow-up. Regression analyses examined relationships of regular walking and walking maintenance with perceived attributes of neighborhood destinations and pedestrian environments. Results Regular walking at baseline was significantly associated with availability of shops (odds ratio [OR] = 1.13, 95% confidence interval [CI] = 1.04–1.22), many alternative routes (OR = 1.12, 95% CI = 1.01–1.23), park or nature reserve (OR = 1.13, 95% CI = 1.02–1.26), bicycle or walking tracks (OR = 1.08, 95% CI = 1.00–1.17), and feeling safe to walk (OR = 1.18, 95% CI = 1.01–1.38). Maintenance of regular walking was associated with the availability of multiple alternative routes (OR = 1.19, 95% CI = 1.03–1.38). Having many alternative routes and walking tracks was associated with walking maintenance among those who were not or had stopped working. Conclusions Neighborhood destinations (shops and parks) and pedestrian environments (alternative routes, walking trails, and safety from crime) were found to be associated with regular walking, but only pedestrian environment attributes were found to be related to the maintenance of regular walking. Further evidence from prospective studies is required to identify other neighborhood environmental attributes that might support walking maintenance.